Results on Invariant Submanifolds of Hyperbolic Kenmotsu Manifolds - Aishwarya, C.; Venkatesha, V. (Communications in Mathematics and Applications, 2024)
In this paper, our main focus was on studying the geodesic property of invariant submanifolds of Hyperbolic Kenmotsu manifolds. We also investigated different conditions regarding the second fundamental form \(π\) and established its equivalence. These conditions included being 2-semiparallel, pseudoparallel, 2-pseudoparallel, Ricci-generalized pseudoparallel and 2-Ricci-generalized pseudoparallel.